Hygroscopic equilibrium of microencapsulated extract of passion fruit seed and its effect on the antioxidant capacity - Silva, Marcos Vieira da [UNESP]; Oliveira, Franciely dos Santos de; Demczuk Junior, Bogdan; Isidoro Haminiuk, Charles Windson; Visentainer, Jesui Vergilio [UNESP] (Wiley-Blackwell, 2018)
The hygroscopic behavior of microcapsules of antioxidant extract of defatted passion fruit seed, produced using spray drying technique, was analyzed at 20 and 40 degrees C by the static method with saturated saline solutions. The isosteric heat of sorption of the microcapsules, concentration of phenolic compounds and piceatannol, and the antioxidant capacity using ABTS and DPPH methods were measured during storage at different relative humidities. The isotherms were classified as GAB isotherms, exhibiting a Type II behavior. Isosteric heat of sorption decreased when the relative humidity increased and critical equilibrium moisture reached 61%. The microencapsulated extracts retained their antioxidant capacities within the evaluated conditions, what suggests that it may be applied in food at any of these water activity values. Practical applicationsPiceatannol is a stilbene with expressive antioxidant capacity which can be found in passion fruit seeds. In this work, the seeds were used to obtain the crude hydroethanolic extract which was microencapsulated by spray drying. The hygroscopic behavior of the microencapsulated extract of piceatannol was evaluated by fitting the data on different isotherm theoretical models. It was possible to verify the interference of the water activity in the antioxidant capacity and establish a relationship with possible critical storage conditions of the microencapsulated extract.